2016
DOI: 10.1002/biot.201600649
|View full text |Cite
|
Sign up to set email alerts
|

Structure and function of the N‐terminal domain of Ralstonia eutropha polyhydroxyalkanoate synthase, and the proposed structure and mechanisms of the whole enzyme

Abstract: Polyhydroxyalkanoates (PHAs) are natural polyesters synthesized by numerous microorganisms as energy and reducing power storage materials, and have attracted much attention as substitutes for petroleum-based plastics. In an accompanying paper, the authors reported the crystal structure of the C-terminal domain of Ralstonia eutropha PHA synthase (PhaC1). Here, the authors report the 3D reconstructed model of full-length of R. eutropha PhaC1 (RePhaC1 ) by small angle X-ray scattering (SAXS) analysis. The catalyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
19
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 34 publications
4
19
0
Order By: Relevance
“…Transmission electron microscopic investigation confirmed that PHB granules in R. eutropha colocalized with the bacterial nucleoid (29). Attachment of PhaM to the PHB synthase PhaC was recently confirmed in three other laboratories (17,30,31). Binding of PHB granules to the nucleoid as a scaffold enables the cells to equally distribute PHB/PHA granules to daughter cells during cell division.…”
mentioning
confidence: 68%
See 1 more Smart Citation
“…Transmission electron microscopic investigation confirmed that PHB granules in R. eutropha colocalized with the bacterial nucleoid (29). Attachment of PhaM to the PHB synthase PhaC was recently confirmed in three other laboratories (17,30,31). Binding of PHB granules to the nucleoid as a scaffold enables the cells to equally distribute PHB/PHA granules to daughter cells during cell division.…”
mentioning
confidence: 68%
“…PhaC of Ralstonia eutropha has been solved (16)(17)(18). The finding of so many proteins with different functions on the PHB granule surface has led to the classification of PHB granules as multifunctional units, and the designation carbonosomes has been proposed for these organelle-like structures (19).…”
mentioning
confidence: 99%
“…It has been my great pleasure to read the two papers entitled "Crystal structure of Ralstonia eutropha polyhydroxyalkanoate synthase C-terminal domain and reaction mechanisms" by Kim et al [1], and "Structure and function of the N-terminal domain of Ralstonia eutropha polyhydroxyalkanoate synthase, and the proposed structure and mechanisms of the whole enzyme" by Kim et al [2].…”
Section: Unveiling the 30-year Mystery Of Polyhydroxyalkanoate (Pha) mentioning
confidence: 99%
“…Kim et al [2] then for the first time report the 3D reconstructed model of full length PHA synthase from R. eutropha, and performed several biochemical studies. These two studies provide feasibility for rational engineering of PHA synthase toward more efficient production of bioplastics, more broad PHA structure diversity and possibly controllable PHA molecular weights.…”
Section: Unveiling the 30-year Mystery Of Polyhydroxyalkanoate (Pha) mentioning
confidence: 99%
“…This special issue firstly brings you two back-to-back papers from Professor Kyung-Jin Kim and Professor Sang Yup Lee [1,2] who have unveiled the 30-year mystery of polyhydroxyalkanoate (PHA) synthase. The studies report the crystal structure of PHA synthase from Ralstonia eutropha, the best studied bacterium for PHA production, as well as the structural basis for the detailed molecular mechanisms of PHA biosynthesis.…”
mentioning
confidence: 99%